Practical Guide for Mainstreaming Gender in Multi-Stakeholder Platforms in Agri-Food Systems - Cosmas, Lutomia; Ouko, Kevin; Nchanji, Eileen (CGIAR Initiative on Gender Equality, 2024)
This guide provides comprehensive and practical strategies, tools, and best practices for mainstreaming gender in the design, implementation, and evaluation of multi-stakeholder platforms (MSPs) within agrifood systems for promotion of equity, enhancing collaborative outcomes, and contributing to sustainable agricultural development. These platforms are designed to facilitate collaborative efforts among diverse stakeholders, ensuring that gender equality is a central focus in addressing agricultural and food security challenges. It designed to enable practitioners to understand gender issues in agri-food systems and guide them on how to address the challenges by taking actionable steps to mainstream gender in MSPs for sustainable and inclusive development.